Comparison of temporalis fascia and tragal cartilage grafts in type 1 tympanoplasty in elderly patients. Issue 3 (June 2019) - Guler, Ismail; Baklaci, Deniz; Kuzucu, Ihsan; Kum, Rauf Oguzhan; Ozcan, Muge
Abstract: Objective: To investigate the success rates and hearing outcomes of temporalis fascia and tragal cartilage grafts used for type-1 tympanoplasty in the elderly (³65 years) Methods: The medical records of 73 elderly patients who underwent type-1 tympanoplasty at our center between January 2010 and June 2017 were retrospectively reviewed for age, gender, perforation side, presence of contralateral perforation, type and location of perforation, graft material types, preoperative and postoperative hearing levels, and length of follow-up. Results: The graft success rate was 83.5% (61 patients) for the entire group, 76.2% (32 patients) for the fascia group, and 93.5% (29 patients) for the cartilage group. The success rate for the cartilage group was significantly higher than that for the fascia group ( P  = 0.048). The mean hearing gain was 12.5 ± 7.6 and 8.9 ± 6.1 dB in the fascia and cartilage groups, respectively, and postoperative ABG was 10 dB or better in 29 (69.0%) and 19 (61.3%) patients, respectively. The mean hearing gain was significantly higher in the fascia group than in the cartilage group ( P  = 0.028), whereas the mean ABG was significantly higher in the cartilage group than in the fascia group ( P  = 0.009). The functional success rates were similar in both groups ( P  = 0.490). Conclusion: Tympanoplasty is a safe and effective procedure in elderly patients with a 83.5% of graft success rate. Tragal cartilage may be the first choice of graft material due to its high success rates. The functional outcomes did not show significant differences between the fascia and cartilage groups.